1993
DOI: 10.3109/00048679309075805
|View full text |Cite
|
Sign up to set email alerts
|

The Edinburgh Postnatal Depression Scale: Validation for an Australian Sample

Abstract: One hundred and three post-partum women completed the Edinburgh Postnatal Depression Scale (EPDS) and were interviewed using the Diagnostic Interview Schedule. A cut-off score of 12.5 on the Edinburgh Postnatal Depression Scale identified all nine women who reached criteria for major depression. At this threshold the sensitivity (the percentage of true "cases" identified) of the EPDS was 100%, its specificity (the percentage of true "non-cases" identified as such) 95.7% and its positive predictive value (the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
217
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(225 citation statements)
references
References 12 publications
3
217
0
2
Order By: Relevance
“…Our study of the Persian version of EPDS suggested that the best cutoff scores for major depression and combined depression were 12=13 and 11=12, respectively (Table 1). In studies by Cox et al (1987), Boyce et al (1993), Lee et al (1998), and others (Eberhard-Gran et al 2001), the same cutoff score (i.e., 12=13) has been recommended. It must be mentioned that in this cutoff, 4.7% of the cases remained undiagnosed and 12.1% were falsely labeled as major depressives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study of the Persian version of EPDS suggested that the best cutoff scores for major depression and combined depression were 12=13 and 11=12, respectively (Table 1). In studies by Cox et al (1987), Boyce et al (1993), Lee et al (1998), and others (Eberhard-Gran et al 2001), the same cutoff score (i.e., 12=13) has been recommended. It must be mentioned that in this cutoff, 4.7% of the cases remained undiagnosed and 12.1% were falsely labeled as major depressives.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that it is valid and reliable as a screening tool for postpartum depression (Cox et al 1987). Since 1987 numerous validation studies have been carried out with most of them reporting satisfactory psychometric properties (Harris et al 1989;Murray and Carothers 1990;Boyce et al 1993;O'Hara et al 1994;Gubash et al 1997;Guedeney and Fermanian 1998;Berle et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Both the EPDS and the PHQ-9 have been validated against formal psychiatric interviews in several previous studies. [13][14][15][16][17][18]25,26,28,39,41,42,46 …”
Section: Discussionmentioning
confidence: 99%
“…The Edinburgh Postnatal Depression Scale (EPDS) is a widely used, 10-item rating scale developed for the detection of depression in postpartum women 24 and has been validated for an Australian sample 25 . The other questionnaire used, the Profile of Mood States (POMS), is a 65-item analytically-derived factor-inventory 26 which measures six dimensions of mood including five negative ratings (tension-anxiety, anger-hostility, fatigue-inertia, confusion-bewilderment, depression-dejection) and one positive rating of mood, vigour-activity.…”
Section: Operative Intervention and Mother-infant Interaction 1069mentioning
confidence: 99%